PENGARUH FAKTOR-FAKTOR DALAM DIMENSI FRAUD TRIANGLE TERHADAP PERILAKU KECURANGAN AKADEMIK MAHASISWA (STUDI KASUS PADA MAHASISWA MANAJEMEN UNIVERSITAS ALMA ATA YOGYAKARTA TAHUN 2020) - Tristiana, Ilvira (IJMA (Indonesian Journal of Management and Accounting), 2021)
This study is an empirical study to determine the effect of pressure, opportunity, and rationalization on academic cheating behavior in management study program students at Alma University, Yogyakarta. The type of research used in this study is a type of quantitative research. The object of this research is Alma Ata University with Management Study Program students as the subject. The sample used is 72 respondents with a population of 90 management students. After testing the results, the values obtained are as follows: the value of t-count>t-table (4.403>1.995) for the pressure variable, the value of t-count>t-table of (2.643>1.995) for the opportunity variable, the value of t-count < t-table (-0.373 <1.995) for the rationalization variable and the value of f-count> t-table (24.556> 2.740) for the three independent variables on the dependent variable. The conclusion of this study is that the pressure and opportunity variables have a significant and positive effect on students' academic cheating behavior, so the greater the value of the influence of the pressure and opportunity variables partially and the influence of pressure, opportunity, rationalization together on the academic cheating variable, the greater the student's opportunity to committing academic fraud is also getting bigger.